Taxonomy and Cladistic Analysis of Plakobranchidae (Gastropoda: Sacoglossa) - Galvão Filho, Hilton de Castro (2018)
The comprehension of the evolutionary history of the order Sacoglossa is fundamental to understand the adaptive radiation of Heterobranchia, the most morphologically heterogeneous group in Gastropoda. Sacoglossans form a well-supported monophyletic group, but the relationship of its internal clades is still confused. Plakobranchidae is the most diverse family and the main systematic problem of Sacoglossa since the lack of detailed descriptions provided many synonyms and invalid taxa from genus to species level. The family Plakobranchidae resulted in a monophyletic group only in few phylogenetic hypotheses of Sacoglossa. However, either molecular or morphological data were usually analyzed to reconstruct Sacoglossa phylogeny, while an integrative approach has never been applied for such purpose. A total 42 species, including 30 species of Plakobranchidae, 10 related species in Sacoglossa and other two heterobranchs, was analyzed to test the monophyly of Plakobanchidae and the relationship of its internal clades. A parsimonious phylogenetic analysis was performed in TNT considering 109 characters of external morphology, internal anatomy and ecology data. Molecular partial sequences of two mitochondrial (COI, 16S) and three nuclear (H3, 18S and 28S) genes were used to build a phylogenetic hypothesis under Bayesian Inference and Maximum Likelihood criteria. One final BI analysis was performed with a combined matrix with molecular, morphological and ecological data of all analyzed taxa. Plakobranchidae resulted as monophyletic only in morphological and combined data, but the monophyletic status of the genera Plakobranchus van Hasselt, Thuridilla Bergh and Elysia Risso, 1818 was fully supported by all analyses. Species within the multi-diverse Elysia form similar clades in all different analysis matching with prior synonymized names, meaning that old names might be resurrected for a better explanation of the natural history of this genus.